2014
DOI: 10.1039/c4an01060d
|View full text |Cite
|
Sign up to set email alerts
|

Concentration dependence of translational diffusion coefficients for globular proteins

Abstract: This investigation examines published results of traditional diffusion experiments on ovalbumin and bovine serum albumin to determine the extent to which assumed concentration independence of the translational diffusion coefficient is a reasonable approximation in the analysis of boundary spreading in sedimentation velocity experiments on proteins. Although significant positive concentration dependence of the diffusion coefficient (D) for both proteins is predicted by current theories, none has been detected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 59 publications
(131 reference statements)
1
23
0
Order By: Relevance
“…The anomalously high diffusion coefficient for degludec at low ionic strength, I , appears to be due to the effects of non-ideality (see Harding & Johnson 30 & Scott et al . 31 ) through unsuppressed charge repulsion effects. Upon the addition of salt and increase of I to approximate physiological conditions, these electrostatic interactions are suppressed, reducing the apparent diffusion coefficient.…”
Section: Discussionmentioning
confidence: 99%
“…The anomalously high diffusion coefficient for degludec at low ionic strength, I , appears to be due to the effects of non-ideality (see Harding & Johnson 30 & Scott et al . 31 ) through unsuppressed charge repulsion effects. Upon the addition of salt and increase of I to approximate physiological conditions, these electrostatic interactions are suppressed, reducing the apparent diffusion coefficient.…”
Section: Discussionmentioning
confidence: 99%
“…Scott et al [62] suggested an expression for the diffusion coefficient corresponding to Eq. (4.18) with D 0 replaced by D SE .…”
Section: Generalized Stokes-einstein Relationmentioning
confidence: 99%
“…Of additional concern is the assumed concentration-independence of the translational diffusion coefficient, an approximation that has been rendered difficult to verify by the essential demise of procedures for measuring D under the constraints of constant temperature and solvent chemical potential [25]. Although attention to these two aspects is clearly required in future studies attempting to take advantage of the suggested procedure, the present theoretical considerations have …”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 96%